Herding behavior in real estate markets: Novel evidence from a Markov-switching model - Babalos, Vassilios; Balcilar, Mehmet; Gupta, Rangan (Elsevier Science Bv, 2015)
Employing a dynamic model that captures herding under different market regimes we provide novel evidence on the herding behavior of US-listed Real Estate Investment Trusts (REITs). Estimates of herding behavior are derived using a Markov regime-switching model. Although static herding model rejects the existence of herding in REITs markets estimates of the regime-switching model reveal substantial evidence of herding behavior under the crash regime for almost all sectors. Most interestingly we observe a shift from negative herding behavior during low and high volatility regimes to positive herding behavior under crash regime for almost all REITs sectors. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Cross sectional dispersion; Market stress; Herding; REITs; Regime switching